PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI KASIR BERBASIS WEB PADA TOKO SEMBAKO ABC - Lolanda Hamim Annisa; Amalia Fitri; Faiz Fadhlurrohman; Fuadz Misbahul Amin; Gilang Aristyawan; Khalimatus Sadiyah (LP3M Universitas Putra Bangsa, 2026)
This research aims to address common challenges faced by grocery stores through the development of a web-based cashier application using the Greedy algorithm for optimizing MSME management. While offering significant benefits, challenges such as internet dependency and data security need to be addressed. The research focuses on continual development with better adaptation to MSME needs. The application leverages the Greedy algorithm for inventory efficiency and enhanced customer satisfaction. The goal is not only to improve operational efficiency but also to provide a competitive edge through improved customer experience, market access, financial management, and debt and credit management.